A super wear-resistant RTP pipe and its production process

By using spherical nanoalumina grafted glass fibers as wear resistance agents in the inner layer of the RTP pipe, combining polyolefin elastomer and silane coupling agents, a reinforced network structure is formed, which solves the problem of wear during transportation and significantly improves wear resistance.

CN118667252BActive Publication Date: 2025-03-04SHANXI CHANGAN YINGLI ENERGY STORAGE PIPE CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410973428.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-03-04
Estimated Expiration
2044-07-19

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of pipeline processing and forming, in particular to a super wear-resistant RTP pipe and its production process. A super wear-resistant RTP pipe comprises a wear-resistant inner layer, and the wear-resistant inner layer comprises the following raw materials in parts by weight: 50-90 parts of polyolefin elastomer, 2-8 parts of wear-resistant agent, 2-5 parts of lubricant, and 6-11 parts of silane coupling agent; the wear-resistant agent is a spherical nano-alumina grafted glass fiber wear-resistant agent. The production process of super wear-resistant RTP pipe is: S1. Add the wear-resistant agent to the polyolefin elastomer, mix, and then add the lubricant and silane coupling agent, mix again to obtain a mixture; S2. Plasticize, extrude, shape and cool the mixture to obtain a wear-resistant inner layer; S3. Wrap glass fiber around the wear-resistant inner layer; S4. Extrude an outer protective tube outside the glass fiber. The wear rate of the wear-resistant layer of the RTP pipe of this application can reach 0.5-1.8%, and it has excellent wear resistance, which is suitable for the transportation of slag slurry in the coal mining industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of pipeline processing and forming, and in particular to a super wear-resistant RTP pipe and a production process thereof. Background Art

[0002] Continuous fiber reinforced thermoplastic pipes (RTP) have always been a hot research direction in the international pipeline field. This is because RTP pipes can not only give full play to the high strength of fibers and withstand high pressure, but also maintain the good flexibility and corrosion resistance of thermoplastics. They have a broad market in the application of high-pressure pipes such as oil pipelines, gas pipelines, water supply and drainage pipes, etc.

[0003] The traditional RTP pipe is divided into three layers. The innermost and outermost layers are thermoplastic materials, and the middle is a reinforcement layer. The method used is to first extrude the thermoplastic inner layer tube, then wrap the reinforcement layer on the inner layer tube, and finally extrude the outer surface protective layer. The commonly used thermoplastic material on the market is polyolefin.

[0004] When RTP pipes are used for transportation, the transported materials will directly contact the inner layer of the pipes. In the coal mining industry, when transporting slurry, the slurry will cause wear to the inner layer of the pipes, affecting the service life of the pipes. Therefore, it is necessary to improve the wear resistance of the pipes.

[0005] The Chinese patent with application number 201611266240.1 discloses a heat-conductive and wear-resistant composite pipe. Dicumyl peroxide is used as an initiator and maleic anhydride is used as a grafting monomer to graft and modify PB to obtain a grafted blend PB-g-MAH, which is then blended with HDPE as a matrix resin, and an amorphous polymer PB resin, nano-metal nitride with high thermal conductivity, inorganic non-metallic filler (molybdenum disulfide, ultrafine carbon black, nano-ceramic powder) and nucleating agent calcium stearate are added to improve the thermal conductivity and wear resistance of the composite material. The nucleating agent stearate can effectively prevent the decrease in the mechanical strength of the composite pipe, ensure that the processing fluidity of the material after blending is increased, and does not reduce the tensile strength, flexural elasticity, impact strength and friction resistance of the material. The addition of inorganic fillers can reduce the friction coefficient of the pipe, improve its wear resistance, and play a role in reducing wear and resistance. The Chinese patent with application number 201611270355.8 discloses a wear-resistant polyethylene composite pipe, which is made of the following raw materials in parts by weight: 100 parts of HDPE, 6-12 parts of molybdenum disulfide treated with a coupling agent, 1-5 parts of nano-ceramic powder, 1-5 parts of ultrafine carbon black, 2-7 parts of polytetrafluoroethylene, and 0.5-1.0 parts of calcium stearate. The present invention improves the wear resistance of the HDPE pipe and improves the flowability of the HDPE pipe without affecting other properties of the pipe by adding a wear-resistant modifier to the HDPE, making it easier to form and process, and the surface of the produced pipe is brighter and smoother, which is more suitable for conveying solid-liquid mixtures, and can avoid scratches caused during loading, unloading, transportation and installation.

[0006] The above-mentioned prior art solutions have the following defects: when adding inorganic anti-wear agents, calcium stearate nucleating agents need to be added to ensure processing performance, but the solubility of calcium stearate nucleating agents in polyolefin materials may be limited, and uneven dispersion or aggregation of particles may occur, affecting the uniformity and mechanical properties of the material. Summary of the invention

[0007] In order to improve the wear resistance of the inside of the RTP pipe, the present application provides a super wear-resistant RTP pipe and a production process thereof.

[0008] In the first aspect, the present application provides a super wear-resistant RTP pipe, which adopts the following technical solutions:

[0009] A super wear-resistant RTP pipe, comprising a wear-resistant inner layer, wherein the wear-resistant inner layer comprises the following raw materials in parts by weight: 50-90 parts of a polyolefin elastomer, 2-8 parts of an anti-wear agent, 2-5 parts of a lubricant, and 6-11 parts of a silane coupling agent;

[0010] The wear-resistant agent is a spherical nano-alumina grafted glass fiber wear-resistant agent.

[0011] By adopting the above scheme, polyolefin elastomer is used as the matrix. The polyolefin elastomer itself has excellent wear resistance. The wear resistance of the wear-resistant inner layer is further improved by adding a wear-resistant agent.

[0012] Spherical nano-alumina grafted glass fiber is used as a wear-resistant agent. Glass fiber has the characteristics of high strength and high toughness, which can improve the wear resistance of the wear-resistant layer. Spherical nano-alumina is grafted on the glass fiber to form a special "ball" structure. Under the coordination of silane coupling agent and "ball" effect, the wear-resistant agent is effectively dispersed in the polyolefin elastomer matrix to form a reinforced network. This structure can prevent or reduce the local deformation of plastics when subjected to force, thereby reducing wear.

[0013] Furthermore, the weight ratio of the anti-wear agent to the polyolefin elastomer is 1:(15-20).

[0014] By adopting the above scheme, the wear resistance of the wear-resistant layer depends on the effective dispersion of the wear-resistant agent in the polyolefin elastomer. The ratio of the wear-resistant agent to the polyolefin elastomer is limited so that the wear-resistant agent can be more evenly dispersed in the polyolefin elastomer matrix, thereby improving the wear resistance of the wear-resistant layer without reducing the mechanical properties of the wear-resistant layer due to the agglomeration of the wear-resistant agent.

[0015] Furthermore, the preparation method of the spherical nano-alumina grafted glass fiber wear resistant agent is:

[0016] 1) Nano-alumina activation

[0017] Adding spherical nano-alumina and glutaric acid into a solvent, performing ultrasonic dispersion, filtering and washing after the reaction, and obtaining glutaric acid-nano-alumina;

[0018] 2) Glass fiber hydroxylation

[0019] Adding glass fiber and hydroxypropanol into a solvent to react, introducing hydroxyl groups on the surface of the glass fiber, filtering and washing, and obtaining hydroxyl-glass fiber;

[0020] 3) Esterification reaction

[0021] The glutaric acid-nano alumina obtained in step 1) and the hydroxyl-glass fiber obtained in step 2) are subjected to esterification reaction to obtain a nano-spherical alumina grafted glass fiber wear-resistant agent.

[0022] By adopting the above scheme, glutaric acid is used to react with nano-alumina, and the carboxyl group in the glutaric acid and the aluminum ion in the nano-alumina are chelated and coordinated, so that the glutaric acid and the nano-alumina are bridged in the form of carboxylate, and glutaric acid-modified nano-alumina is obtained, and carboxyl groups are introduced on the alumina. The glass fiber is hydroxylated to introduce hydroxyl groups on the surface of the glass fiber. Then, glutaric acid-nano-alumina and hydroxyl-glass fiber are subjected to esterification reaction, and spherical nano-alumina is grafted on the glass fiber. The spherical nano-alumina is combined with the glass fiber through chemical bonds, and the bonding strength of the spherical nano-alumina and the glass fiber is improved, and the "ball" structure of the wear-resistant agent in the wear-resistant layer is ensured, which is conducive to ensuring the wear resistance of the wear-resistant layer.

[0023] Furthermore, the weight ratio of the nano-alumina to the glass fiber is 1:(6-9).

[0024] By adopting the above scheme, the ratio of nano alumina to glass fiber is limited. The ratio of nano alumina to glass fiber determines the shape of the obtained wear-resistant agent. The structure of the wear-resistant agent obtained within the ratio range specified in this application performs better in improving the wear resistance of the wear-resistant layer.

[0025] Furthermore, the nano-alumina particle size is 20-30nm.

[0026] Furthermore, the glass fiber has a length of 1-5 mm and a particle size of 0.03-0.07 mm.

[0027] By adopting the above scheme, the particle size of nano-alumina and the aspect ratio of glass fiber jointly determine the morphology of the obtained wear-resistant agent. Within the matching range specified in the present application, the structure of the obtained wear-resistant agent performs better in improving the wear resistance of the wear-resistant layer.

[0028] Furthermore, based on the total weight of the polyolefin elastomer, the polyolefin elastomer includes the following raw materials in parts by weight: 5-15 parts of fluorine-containing rubber, 5-10 parts of EPDM rubber, 15-30 parts of polyethylene-propylene copolymer, 20-30 parts of polyethylene-butene copolymer, 60-90 parts of polyethylene, 0.2-1 parts of organic peroxide, and 0.1-0.7 parts of cross-linking agent.

[0029] By adopting the above scheme, fluorine-containing rubber is added to the polyolefin elastomer to obtain a fluorine-rubber grafted modified polyolefin elastomer, which can reduce the friction coefficient of the polyolefin elastomer and is beneficial to improving the wear resistance of the wear-resistant layer.

[0030] Furthermore, the polyethylene includes polyethylene with a molecular weight of 200,000-500,000 and polyethylene with a molecular weight of 4,000,000-7,000,000 in a weight ratio of 1:(4-8).

[0031] In the second aspect, the present application provides a production process for super wear-resistant RTP pipes, which adopts the following technical solutions:

[0032] A production process for super wear-resistant RTP pipes comprises the following steps:

[0033] S1. The wear agent is added to the polyolefin elastomer, mixed, and then a lubricant and a silane coupling agent are added, and mixed again to obtain a mixture;

[0034] S2. The mixture is plasticized, extruded, shaped and cooled to obtain a wear-resistant inner layer;

[0035] S3. Wrap glass fiber around the wear-resistant inner layer;

[0036] S4. Extrude an outer protective tube outside the glass fiber.

[0037] In summary, this application has the following technical effects:

[0038] Using polyolefin elastomer as the matrix, spherical nano-alumina grafted glass fiber as the wear-resistant agent, nano-alumina grafted glass fiber forms a special "ball" structure. Under the coordination of silane coupling agent and "ball" effect, the wear-resistant agent is effectively dispersed in the polyolefin elastomer matrix to form a reinforced network. This structure can prevent or reduce the local deformation of plastics when subjected to force, thereby reducing wear. The wear rate of the wear-resistant layer obtained can reach 0.5-1.8%. DETAILED DESCRIPTION

[0039] The present application is further described in detail below in conjunction with embodiments.

[0040] Raw materials and intermediate preparation examples

[0041] The raw materials in the examples of this application can be obtained from the market:

[0042] The lubricant is PP wax;

[0043] Silane coupling agent is KH-550:

[0044] Glutaric acid, analytical grade;

[0045] Ethanol solvent, analytical grade;

[0046] Hydroxypropanol, analytical grade;

[0047] The fluorinated rubber is a hexafluoropropylene terpolymer with a molecular weight of 1.5 million, a glass transition temperature of 20°C, and a fracture growth rate of 200%;

[0048] EPDM rubber, density 0.9g / cm 3 , glass transition temperature -65℃, fracture growth rate 300%, hardness 50A;

[0049] Polyethylene-propylene copolymer, density 0.92 g / cm 3 , melting point 140℃;

[0050] Polyethylene-butene copolymer, density 0.91 g / cm 3 , melting point 110℃;

[0051] Organic peroxide, tert-amyl peroxybenzoate;

[0052] Crosslinker, pentaerythritol triacrylate.

[0053] Preparation Example

[0054] Preparation Example I-1

[0055] A spherical nano-alumina grafted glass fiber wear-resistant agent, the preparation method of which is as follows:

[0056] 1) Nano-alumina activation

[0057] Add spherical nano-alumina and glutaric acid to 2 ethanol solvent, perform ultrasonic dispersion, filter and wash after reaction, and obtain glutaric acid-nano-alumina; the weight ratio of spherical nano-alumina to glutaric acid is 1:12; the average particle size of nano-alumina is 20 nm;

[0058] 2) Glass fiber hydroxylation

[0059] The glass fibers were cleaned with ethyl acetate and then rinsed with water; the glass fibers were 1-5 mm long and had an average particle size of 0.07 mm;

[0060] Spray concentrated nitric acid solution on the surface of the cleaned glass fiber, and rinse with water after 5 minutes to obtain activated glass fiber;

[0061] The glass fiber and hydroxypropanol are added into an ethanol solvent to react, a hydroxyl group is introduced on the surface of the glass fiber, and the mixture is filtered and washed to obtain a hydroxy-glass fiber; the ratio of the hydroxypropanol to the glass fiber is 1:10;

[0062] 3) Esterification reaction

[0063] The glutaric acid-nano alumina obtained in step 1) and the hydroxyl-glass fiber obtained in step 2) are subjected to esterification reaction to obtain a nano-spherical alumina grafted glass fiber wear-resistant agent; the weight ratio of the nano-alumina to the glass fiber is 1:6.

[0064] Preparation Example I-2

[0065] Different from Preparation Example I-1, the weight ratio of spherical nano-alumina to glass fiber in Preparation Example I-2 is 1:7.

[0066] Preparation Example I-3

[0067] Different from Preparation Example I-1, the weight ratio of spherical nano-alumina to glass fiber in Preparation Example I-3 is 1:9.

[0068] Preparation Example I-4

[0069] Different from Preparation Example I-1, the weight ratio of spherical nano-alumina to glass fiber in Preparation Example I-4 is 1:12.

[0070] Preparation Example I-5

[0071] Different from Preparation Example I-2, in Preparation Example I-5, the average particle size of the spherical nano-alumina is 25 nm, the length of the glass fiber is 1-5 mm, and the average particle size is 0.05 mm.

[0072] Preparation Example I-6

[0073] Different from Preparation Example I-2, in Preparation Example I-6, the average particle size of the spherical nano-alumina is 30 nm, the length of the glass fiber is 1-5 mm, and the average particle size is 0.03 mm.

[0074] Preparation Example I-7

[0075] Different from Preparation Example I-5, the glass fiber in Preparation Example I-7 has a length of 7-9 mm and an average particle size of 0.05 mm.

[0076] Preparation Example II-1

[0077] A polyolefin elastomer, the preparation method of which is as follows:

[0078] According to the proportions in Table 1, fluorine-containing rubber, EPDM rubber, polyethylene-propylene copolymer, polyethylene-butene copolymer, polyethylene, organic peroxide and cross-linking agent were uniformly mixed, and then subjected to dynamic thermal grafting reaction in a twin-screw extruder at 200° C. to obtain a polyolefin thermoplastic elastomer after granulation.

[0079] Table 1 Polyolefin elastomer raw material ratio table (kg)

[0080]

[0081] Among them, the molecular weight of polyethylene is 300,000.

[0082] Preparation Example II-6

[0083] Different from Preparation Example II-2, the polyethylene in Preparation Example II-6 is a polyethylene with a molecular weight of 300,000 and a polyethylene with a molecular weight of 6,000,000 in a weight ratio of 1:4.

[0084] Preparation Example II-7

[0085] Different from Preparation Example II-2, the polyethylene in Preparation Example II-7 is a polyethylene with a molecular weight of 300,000 and a polyethylene with a molecular weight of 6,000,000 in a weight ratio of 1:8.

[0086] Preparation Example II-8

[0087] Different from Preparation Example II-2, the molecular weight of the polyethylene in Preparation Example II-8 is 6 million.

[0088] Example

[0089] Examples 1-5

[0090] A wear-resistant inner layer, the preparation method of which is:

[0091] S1. According to the raw material ratio in Table 2, the wear agent is added to the polyolefin elastomer, mixed, and then the lubricant and the silane coupling agent are added, and mixed again to obtain a mixture;

[0092] S2. The mixed material is plasticized, extruded, shaped and cooled to obtain a wear-resistant inner layer.

[0093] Table 2 Ratio of raw materials for wear-resistant inner layer of Examples 1-5 (kg)

[0094]

[0095] Among them, the anti-wear agent comes from Preparation Example I-1, and the polyolefin elastomer comes from Preparation Example II-1.

[0096] Examples 6-12

[0097] Different from Example 2, the polyolefin elastomers in Examples 6-12 are respectively from Preparation Examples II-2 to II-8.

[0098] Examples 13-18

[0099] Different from Example 10, the anti-wear agents in Examples 13-18 are respectively from Preparation Examples I-2 to I-7.

[0100] Comparative Example

[0101] Comparative Example 1

[0102] The difference from Example 1 is that in Comparative Example 1, an equal amount of spherical nano-alumina is used as the wear-resistant agent.

[0103] Comparative Example 2

[0104] Different from Example 1, in Comparative Example 2, an equal amount of glass fiber is used as the wear-resistant agent.

[0105] Comparative Example 3

[0106] Different from Example 1, in Comparative Example 3, an equal amount of polyethylene replaces the polyolefin elastomer.

[0107] Performance Testing

[0108] The tensile strength and wear rate of the wear-resistant layer obtained in the embodiment and the comparative example were tested, and the test results are shown in Table 3.

[0109] Table 3 Performance test results

[0110]

[0111] Combining Examples 1-18 with Comparative Examples 1-3 and Table 3, it can be seen that the tensile strength of the wear-resistant layer obtained in Examples 1-18 is not much different from that of the wear-resistant layer obtained in Comparative Examples 1-3, but the wear rate of the wear-resistant layer in Examples 1-18 is significantly lower than that in Comparative Examples 1-3, which indicates that the wear-resistant layer obtained in the present application has better comprehensive performance in terms of mechanical properties and wear resistance, and the RTP pipe made with the wear-resistant layer of the present application is suitable for the transportation of slurry.

[0112] Combining Example 1 with Comparative Examples 1-2 and Table 3, it can be seen that in Comparative Example 1, nano-alumina is used as a wear-resistant agent, and in Comparative Example 2, glass fiber is used as a wear-resistant agent. Compared with the nano-alumina grafted glass fiber in Example 1, the wear resistance of the wear-resistant layer obtained in Comparative Examples 1 and 2 is significantly reduced, which shows that the use of nano-alumina grafted glass fiber can improve the wear resistance of the wear-resistant layer. This may be because the use of alumina alone may reduce the friction coefficient of the wear-resistant layer surface and thus improve the wear resistance. The use of glass fiber alone can also improve the wear resistance, but the effect of improving the wear resistance is not ideal. After nano-alumina is grafted to glass fiber, a special "ball" structure is formed. Under the synergy of the silane coupling agent and the "ball" effect, the wear-resistant agent is effectively dispersed in the polyolefin elastomer matrix to form a reinforced network. This structure can prevent or reduce the local deformation of the plastic when it is subjected to force, thereby reducing wear to a greater extent.

[0113] Combining Examples 1-5 and Table 3, it can be seen that the wear-resistant layers obtained in Examples 1-5 all have good wear resistance, and the wear-resistant layer obtained by the ratio in Example 2 has better wear resistance.

[0114] Combining Example 2, Examples 6-12 and Comparative Example 3, and Table 3, it can be seen that the structure of the polyolefin elastomer affects the wear resistance of the wear-resistant layer, and the wear resistance of the wear-resistant layer obtained by the polyolefin elastomer in Example 10 and Example 11 is better. This may be because the surface friction coefficient of the material made of the polyolefin elastomer in Example 10 and Example 11 is low, and the cross-linking thereof forms an elastomer network that can absorb the impact energy and improve the wear resistance of the material.

[0115] In combination with Examples 13-18 and Table 3, it can be seen that when preparing the wear-resistant agent, the specific physical parameters and ratio of the spherical nano-alumina and the glass fiber will affect the wear resistance of the wear-resistant layer. This may be because the particle size of the nano-alumina, the aspect ratio of the glass fiber, and the ratio of the nano-alumina to the glass fiber jointly determine the morphology of the obtained wear-resistant agent. Within the scope defined in this application, the structure of the obtained wear-resistant agent performs better in improving the wear resistance of the wear-resistant layer.

[0116] Application Examples

[0117] Application Example 1

[0118] A super wear-resistant RTP pipe, the production process of which is:

[0119] S1. According to the raw material ratio of Example 1 in Table 2, the wear-resistant agent is added to the polyolefin elastomer, mixed, and then the lubricant and the silane coupling agent are added, and mixed again to obtain a mixture; the heating temperature of the extruder barrel is zone 1: 160 ° C, zone 2-6: 200 ° C;

[0120] S2. The mixture is plasticized, extruded, shaped and cooled to obtain a wear-resistant inner layer;

[0121] S3. Wrap glass fiber around the wear-resistant inner layer;

[0122] S4. Extrude an outer protective tube outside the glass fiber.

[0123] Application Example 2-18

[0124] Different from Application Example 1, the raw material ratios in Application Examples 2-18 are the same as those in Embodiments 2-18.

[0125] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A super wear-resistant RTP pipe, comprising a wear-resistant inner layer, characterized in that: The wear-resistant inner layer comprises the following raw materials in parts by weight: 50-90 parts of polyolefin elastomer, 2-8 parts of wear-resistant agent, 2-5 parts of lubricant, and 6-11 parts of silane coupling agent; The wear-resistant agent is a spherical nano-alumina grafted glass fiber wear-resistant agent; The preparation method of the spherical nano-alumina grafted glass fiber wear-resistant agent is as follows: 1) Nano-alumina activation Adding spherical nano-alumina and glutaric acid into a solvent, performing ultrasonic dispersion, filtering and washing after the reaction, and obtaining glutaric acid-nano-alumina; 2) Glass fiber hydroxylation Adding glass fiber and hydroxypropanol into a solvent to react, introducing hydroxyl groups on the surface of the glass fiber, filtering and washing, and obtaining hydroxyl-glass fiber; 3) Esterification reaction The glutaric acid-nano-alumina obtained in step 1) is subjected to an esterification reaction with the hydroxyl-glass fiber obtained in step 2) to obtain a nano-spherical alumina-grafted glass fiber wear-resistant agent; The weight ratio of the spherical nano-alumina to the glass fiber is 1:(6-9); The average particle size of the spherical nano-alumina is 20-30 nm; The glass fiber has a length of 1-5 mm and an average particle size of 0.03-0.07 mm; Based on the total weight of the polyolefin elastomer, the polyolefin elastomer includes the following raw materials in parts by weight: 5-15 parts of fluorine-containing rubber, 5-10 parts of EPDM rubber, 15-30 parts of polyethylene-propylene copolymer, 20-30 parts of polyethylene-butene copolymer, 60-90 parts of polyethylene, 0.2-1 parts of organic peroxide, and 0.1-0.7 parts of cross-linking agent.

2. The super wear-resistant RTP pipe according to claim 1, characterized in that: The weight ratio of the anti-wear agent to the polyolefin elastomer is 1:(15-20).

3. The super wear-resistant RTP pipe according to claim 1, characterized in that: The polyethylene includes polyethylene with a molecular weight of 200,000-500,000 and polyethylene with a molecular weight of 4,000,000-7,000,000 in a weight ratio of 1:(4-8).

4. A production process for the super wear-resistant RTP pipe according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. The wear agent is added to the polyolefin elastomer, mixed, and then a lubricant and a silane coupling agent are added, and mixed again to obtain a mixture; S2. The mixture is plasticized, extruded, shaped and cooled to obtain a wear-resistant inner layer; S3. Wrap glass fiber around the wear-resistant inner layer; S4. Extrude an outer protective tube outside the glass fiber.

Citation Information

Patent Citations

  • High-heat conduction anti-wear composite tube

    CN106750814A

  • Wear-resistant polyethylene composite pipe

    CN107057154A

  • Super wear-resistant composite pipe and preparation method thereof

    CN113045810A

  • Modified long glass fiber reinforced polypropylene composite material as well as preparation method and application thereof

    CN114426732A

  • Sulphur-resisting glassfibre reinforced plastics wear-resisting continuous tube

    CN202402825U